Benefits of Psychological Androgyny in Adolescence: The Role of Gender Role Self-Concept in School-Related Well-Being - Korlat, Selma; Holzer, Julia; Schultes, Marie-Therese; Buerger, Sarah; Schober, Barbara; Spiel, Christiane; Kollmayer, Marlene (Frontiers in Psychology, 2022)
It has been repeatedly shown that the extent to which individuals adopt stereotypically masculine and feminine traits in their self-concept impacts their health and well-being. This is especially important in adolescence, when developmental changes and social pressures to conform to stereotypical gender roles can affect psychological functioning. However, previous studies investigating relationship between gender role self-concept and well-being in adolescents focused mostly on general well-being rather than well-being in specific contexts. Given that school is one of the most important contexts for adolescents’ development and well-being, the aim of this study was to investigate differences between adolescents with different gender role self-concepts (masculine, feminine, androgynous and undifferentiated) in school-related well-being. In line with the new conceptualization of well-being uniting hedonic (pleasure attainment and pain avoidance) and eudemonic (self-actualization and having meaningful purpose in one’s life) approaches, the present study used a measure of school-related well-being encompassing five domains suggested in the EPOCH (Engagement, Perseverance, Optimism, Connectedness and Happiness) model as well as a superordinate well-being factor. A total of 999 Austrian adolescents (52.2% girls, Mage = 13.79, SDage = 1.53) answered inventories assessing adolescents’ gender role self-concept (GRI-JUG) and school-related well-being (EPOCH-G-S). The results supported the androgyny model of well-being, showing clear advantages of having both positive masculine and feminine qualities in one’s self-concept for optimal levels of school-related well-being. In addition, our results indicated the strong importance of femininity in adolescence and the school context. Theoretical and practical implications are discussed.